FRASA NOMINA DALAM BAHASA DAYAK KANAYATN - Dara, Agustina Angela; Sukamto, Sukamto; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPhrase is a composite or group of words made up of two or more words that have a grammatical meaning (change of meaning based on the context). Noun phrase is a group or composite of noun words formed by expanding a noun, the group of words forms extension of the noun which can be either as an additional or a complementary information. The core element of noun phrase is the noun word. Dayak Kanayatn (Kendayan) is a language spoken by the Kanayatn – the Dayaknese who speak this Banana'/ Ahe language. The purpose of this study is to describe the distribution, category, and the use of noun phrase in BDK. The method used in this research is descriptive method with qualitative approach. The source of data in this study was BDK spoken by the informant while the data of the noun phrase was gathered form BDK spoken by the informant. The techniques used in this study were transcription or copying, translation, and data classification, while the tool used in the study was laptop. Based on data analysis, the results of this study are as follows: (1) endocentric coordinative phrase and attributive endocentric phrase were identified in the distribution of noun phrase element; (2) In the noun phrase category it found out that Nwas followed by N, N was followed by V, N was followed by Bil, N was followed by Ket, N was followed by FD, N was preceded by Bil, and N was preceded Sd (3) the use of noun phrase occupied the position of subject, predicate, object, and description.Keywords: phrase, noun phrase, Dayak language Kanayatn (BDK).